The Effectiveness of Massage Therapy as Pain Management During the First Stage of Labor: A Literature Review - Nessi Meilan; Tris Eryando (Mulawarman International Conference on Tropical Public Health, 2025)
Labor pain is a subjective experience caused by uterine muscle ischemia, stretching and traction of the uterine ligaments, traction of the ovaries, fallopian tubes, and lower uterine distension, pelvic floor muscles, and perineum. The labor pain that occurs can lead to anxiety and stress in the mother, excessive worry, prolonged first stage of labor, and traumatic experiences during childbirth. Endorphin massage is a non-pharmacological therapy, a modification of Indonesia's cultural heritage, used to reduce the intensity of labor pain in the first stage. Objective: To determine the effectiveness of endorphin massage on pain levels during labor, in order to provide scientific evidence for the management of labor pain during the first stage, and to support safe, effective, and evidence-based midwifery practices. Methodology: A literature review with a study design of Randomized Controlled Trials (RCT) and Quasi-Experimental studies. Literature searches were conducted using Google Scholar, PubMed (Medline), ProQuest, ScienceDirect, and Scopus, covering publications from 2018 to 2025 in both Indonesian and English. Study selection was based on inclusion criteria derived from titles, abstracts, and full texts, and on the studies' feasibility assessment, which were then analyzed based on their findings. Results: Ten journals met the criteria, and after analysis, eight studies were deemed suitable. Pain measurement was conducted using the Numeric Rating Scale (NRS) or Visual Analog Scale (VAS). Endorphin massage was performed for 10 minutes on the back and waist of laboring mothers during the first stage, three times. The results showed that the pain intensity before the endorphin massage was 7.27, and after the massage, it decreased to 4.93. This demonstrates that endorphin massage significantly reduces the intensity of labor pain. Conclusion: Endorphin massage is a complementary therapy that can be used as part of the management of labor pain during the first stage.